Pedobacter nyackensis sp. nov., Pedobacter alluvionis sp. nov. and Pedobacter borealis sp. nov., isolated from Montana flood-plain sediment and forest soil - Gordon, Nathan S.; Valenzuela, Alejandra; Adams, Sandra M.; Ramsey, Philip W.; Pollock, Jarrod L.; Holben, William E.; Gannon, James E. (International Journal of Systematic and Evolutionary Microbiology, 2009)
Three Gram-negative, rod-shaped, non-spore-forming eubacterial strains were isolated in western Montana, USA, and subjected to taxonomic studies. Strains NWG-II14T and NWER-II11T were isolated from hyporheic sediments of a large alluvial flood plain, whereas strain G-1T was isolated from a conifer forest soil. On the basis of 16S rRNA gene sequence similarity, strains NWG-II14T, NWER-II11T and G-1T were shown to belong to the family Sphingobacteriaceae and are most closely related to various species of the genus Pedobacter. The results of molecular, physiological and biochemical tests allowed genotypic and phenotypic differentiation of these three strains from 23 Pedobacter species with validly published names. The three isolates therefore represent novel species, for which the names Pedobacter nyackensis sp. nov. (type strain NWG-II14T =DSM 19625T =LMG 24260T), Pedobacter alluvionis sp. nov. (type strain NWER-II11T =DSM 19624T =LMG 24258T) and Pedobacter borealis sp. nov. (type strain G-1T =DSM 19626T =LMG 24259T) are proposed.